Development of School Profile Video at SMP Nusantara Kendari - Samsul Saliha; Zila Razilu; Hendra Nelva Saputra (Jurnal Amal Pendidikan, 2024)
The development of school profile videos is becoming an increasingly essential aspect of technology. Making a school profile video is an effort to convey information about educational institutions, including academic programmes, facilities, and student life in an attractive visual form. The purpose of this research is to create a video profile of SMP Nusantara Kendari. The research method used is the Villamil-Molina method. The stages in the Villamil-Molina method are divided into five parts, namely development, preproduction, production, post production, and delivery. SMP Nusantara Kendari profile video The school profile video has been developed according to the Villamil-Molina method and produced a video with a duration of 3 minutes 14 seconds. This school profile video consists of information on facilities and infrastructure, number of teachers, learning activities and school excellence. The results of the media expert test obtained an average percentage value of 78.33% which can be interpreted that the school profile video developed is feasible and meets the media assessment indicators that focus on the integration of text and images, video shooting quality, video presentation, and video editing techniques.